Examen especial a la cuenta cartera vencida del gobierno autónomo descentralizado municipal del cantón Aguarico, provincia de Orellana durante el periodo 2014 - Cordovillo Ocaña, Lourdes Lucila (2016)
The thesis entitled "SPECIAL REVIEW ACCOUNT NONPERFORMING LOANS GOVERNMENT AUTONOMOUS DECENTRALIZED CITY OF CANTON AGUARICO, ORELLANA PROVINCE FOR THE PERIOD 2014", was aimed at evaluating the efficiency and effectiveness and the degree of compliance control system internal because the portfolio has expired, to detect possible irregularities and establish corrective measures to be towards the improvement of municipal management and submit the final report on the results once. With the special examination were complied with the objectives through an internal analysis to the entity for procedures, methods and processes used in collection of taxes, fees and other services to assess the degree of compliance of laws regulations and regulations applicable to the account nonperforming loans. Techniques and procedures applied in the audit documentation, records and evidence presented in the collection of nonperforming loans; finally the report with the respective comments, conclusions and recommendations resulted from the findings made in the Special Examination was performed. In conclusion of the work performed it provides that lacks internal control and not fully met the regulations; having a high level of risks therefore there is a low confidence. For which alternatives are raised to improve collection management.